Analisis Hadis Pengajaran Berbasis Masalah dengan Pendekatan Tarbawi - Amrulloh, Amrulloh; Ahmadi, Rizqa; Putra, Miftakhul Ilmi Suwignya (Jurnal Pendidikan Islam, 2021)
This study is motivated by the chapter on á¹ará¸¥ al-â€˜Älim al-masâ€˜ala â€˜ala al-mutaâ€˜allim (problem posing by the teacher to the students) in JÄmiâ€˜ bayÄn al-â€˜ilm wa faá¸lihi by Ibn â€˜Abd al-Barr (d. 463 AH/1071 AD) which contains three á¸¥adÄ«ths and three â€˜ulamÄâ€™ vows, which at first glance are identical to problem-based learning methods. The purpose of this study is to explore the existence of the á¸¥adÄ«ths about problem posing by the teacher to the students in terms of their authenticity and validity; also to explore and analyze the understanding of the á¸¥adÄ«ths about problem posing by the teacher to the students using the tarbawÄ« approach. This is a library research that is enhanced by the takhrÄ«j approach and the shará¸¥ approach and its contextualization. The results of this study indicate that the á¸¥adÄ«ths are authentic and valid. The results of this study also show that there is a problem-based teaching message in the TarabwÄ« á¸¤adÄ«th which is classified as contextually progressive.